Kreativitas Guru untuk Memanfaatkan Media Pembelajaran pada Bahasa Inggris What Delicious Bakso ! - Fajarisman, Fajarisman; Citra P, Nostalgianti; Wijaya, Pipit Rika; Ariama, Ana (JOEAI (Journal of Education and Instruction), 2023)
This study aims to determine; 1) How does a teacher use learning media in carrying out learning activities in class, especially English 2). How do teachers develop learning media in English learning activities 3) problems faced by teachers in ongoing learning. This study used a qualitative case study approach in which the research subjects were fifth grade students at SD Negeri 3 Kandang Situbondo. Data collection techniques using observation, interviews, documentaries and questionnaires. The results of the research involving school principals, English teachers and fifth grade students, namely; 1) Teachers use learning media that are creative and appropriate to learning to support learning activities; 2) the teacher's way of developing creativity for learning English by considering indicators, the level of student development and the psychological conditions of students; 3) Problems experienced by teachers in utilizing learning media, especially English, such as the condition of busy students, the lack of facilities and infrastructure owned by schools. In conclusion, the use of English learning media is very important in attracting students' interest, curiosity and willingness to learn. Keywords: English, Learning Media, What Delicious Meatballs!